Representações de professores homens na Educação Infantil: reflexões a partir dos filmes um tira no jardim de infância - Santos, Denilson Brito Dos (Universidade Federal do Tocantins, 2022)
This article addresses the presence of men as teachers in early childhood education. The objective is to analyze what are the representations built about the teachers who work in Early Childhood Education using bibliography pertinent to the theme and the analysis of the films A Strip in Kindergarten (1990) and A Strip in Kindergarten 2 (2016). This is qualitative research, using the Cultural History to analyze the practices and representations present in the works analyzed. It was found with this work that the academic literature addresses the estrangement that teachers face when assuming the teaching of babies and young children. This issue is especially linked to gender stereotypes, notions of motherhood and representations of who are people "naturally" responsible and able to exercise the care of children and babies. It was found that all these issues are linked to women, being the most accepted teachers to work with young children and babies. Teachers in Early Childhood Education suffer prejudice and need to stand out and demonstrate competence in their work to be respected and accepted in a territory that is seen as not belonging to them. The film analysis allows us to realize that the representations built in fiction are close to the real issues experienced daily by Brazilian teachers. Finally, it is hoped that the work can contribute to the debates to understand Early Childhood Education as a teaching space also of men and deconstruct gender prejudices linked to the profession.